¿Los Foráneos? Relatos de Población Receptora de Migrantes en una Ciudad Fronteriza (2022)
This research article shows a broad analysis of the situation of migrants in the city of Cúcuta - Norte de Santander (Colombia) and the representations that the receiving citizens have in this border context. The methodological approach of this study was framed from the qualitative-hermeneutic paradigm where the life story was used as a basis for collecting information. The results of the research show that the discourses of the subjects under study legitimise violent actions towards the Venezuelan migrant population. Furthermore, it shows that in the border municipalities, residents naturalise the current situation, to the extent that it seems that the events that occur in this border context are isolated from the reality of those who do not migrate, describing them as "something normal".